Implementasi Manajemen Humas dalam Membangun Hubungan Sekolah dalam Masyarakat di SDN 1 Mangli Jember - Duwi Sakiatul R; Cindy Syafatur R; Hilmia Rina Aminda; Eka Pujawati; Rofiq Hidayat (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the implementation of public relations management in building school-community relations at SDN 1 Mangli. The research highlights the importance of community involvement as a strategic partner in improving the quality of basic education. The theoretical framework is based on the Excellence Theory, community participation theory, and two-way symmetrical communication relevant to the school’s public relations role. The study employs a qualitative approach with a case study design, involving the principal, teachers, school committee, and parents through interviews, observations, and documentation. Data were analyzed using the Miles & Huberman interactive model.The findings indicate that SDN 1 Mangli has implemented public relations management strategically—not only administratively—but also as a means to foster communication, enhance community participation, and strengthen the school’s positive image. However, challenges remain, including the dominance of one-way communication, limited use of digital media, and the absence of measurable evaluation indicators. This research reveals that elementary schools can adopt modern public relations principles. The study implies the need to strengthen two-way symmetrical communication, optimize digital media utilization, and develop measurable evaluation indicators for school public relations programs.